Solid state fermentation composting process of palm kernel cake and Moringa oleifera husk - Kabbashi, Nassereldeen Ahmed; Mat Aris, Muhammad Izzat; Qudsieh, Isam Y. (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Wastes from oil palm industries are produced every year and becoming a great concern, consequently, an urgent development of bio-composting process has been studied and investigated. Bio-composting is an easy and simple process for the environmental friendly decomposition of organic wastes which in turn can be used as manure or fertilizer. The study was concerning about simple composting process using selected substrates, Palm Kernel Cake (PKC) and Moringa oleifera husk. The strains of Phanerochaete chrysosporium, Aspergillus niger and penicillium were used in this experiment. Tray bioreactor was used to test and evaluate the efficiency of composting process by solid state fermentation process. The composting time required for the process to complete was 60 days. Some parameters were determined to evaluate the quality of compost as C/N ratio, pH and germination index. The maturity of the composting could be determined by C/N ratio, pH, and germination index result. The use of PKC and Moringa oleifera husk as mixed substrates is the new composting trial which has not been done by researchers and it has been expected to produce a good result.